2007
DOI: 10.2337/db06-1601
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species as a Signal in Glucose-Stimulated Insulin Secretion

Abstract: One of the unique features of ␤-cells is their relatively low expression of many antioxidant enzymes. This could render ␤-cells susceptible to oxidative damage but may also provide a system that is sensitive to reactive oxygen species as signals. In isolated mouse islets and INS-1(832/13) cells, glucose increases intracellular accumulation of H 2 O 2 . In both models, insulin secretion could be stimulated by provision of either exogenous H 2 O 2 or diethyl maleate, which raises intracellular H 2 O 2 levels. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
436
6
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(493 citation statements)
references
References 54 publications
(59 reference statements)
19
436
6
11
Order By: Relevance
“…Apparently, our in vivo results are in stark contrast to the transient benefits of upregulating antioxidant capacity as shown in vitro [6,7] or during short-term situations [23]. Therefore, this study reveals a long-term metabolic risk of disturbing the balance between intracellular antioxidant defence and ROS formation [9] and cautions against antioxidant strategies to prevent or treat diabetes [9,50]. We have illustrated a decreased UCP2 protein concomitant with an increased mitochondrial potential in the OE islets, suggesting a new function of GPX1 in mitochondria.…”
Section: Discussionmentioning
confidence: 62%
“…Apparently, our in vivo results are in stark contrast to the transient benefits of upregulating antioxidant capacity as shown in vitro [6,7] or during short-term situations [23]. Therefore, this study reveals a long-term metabolic risk of disturbing the balance between intracellular antioxidant defence and ROS formation [9] and cautions against antioxidant strategies to prevent or treat diabetes [9,50]. We have illustrated a decreased UCP2 protein concomitant with an increased mitochondrial potential in the OE islets, suggesting a new function of GPX1 in mitochondria.…”
Section: Discussionmentioning
confidence: 62%
“…The classical ATP elevation-induced insulin closure of K ϩ channels may not be the only player for triggering insulin secretion (14,29). Evidence that ROS might contribute to glucose-stimulated insulin secretion is emerging (25,42). Leloup et al (25) strongly suggested that ROS are stimulators of insulin secretion independently of other products linked to glucose metabolism such as ATP.…”
Section: Discussionmentioning
confidence: 99%
“…(15) showed that the induction of ROS emission from the electron transport chain stimulates insulin release to the same degree as glucose-mediated ATP production. Glucose metabolism has also been shown to increase intracellular ROS levels in rat islets, Min6 (mouse ␤ cell line), and INS-1 832/13 cells (rat ␤ cell line), conditions associated with GSIS (9,12). In addition to the regulation of GSIS-amplifying ROS signals, ROS are also important regulators of UCP2 function itself (1).…”
mentioning
confidence: 99%
“…, generated artificially with menadione) or H 2 O 2 stimulates insulin release (reviewed in Refs. 9,[11][12][13][14]. Furthermore, Leloup et al.…”
mentioning
confidence: 99%